Aboriginal Peoples Survey, 2012 [Canada] - Social and Aboriginal Statistics Division (Borealis, 2013)
The 2012 Aboriginal Peoples Survey (APS) is a national survey of First Nations people living off reserve, Métis and Inuit aged six years and over. The 2012 APS represents the fourth cycle of the survey and focuses on the topics of education, employment and health. It also collects information on language, income, housing and mobility. The 2012 APS collects unique and detailed data on education, employment and health, data which are not available from any other source. For example, although the 2011 National Household Survey collected data on level of education and on major field of study, the 2012 APS addresses additional topics such as number of schools attended, exposure to Aboriginal languages, school climate and support, frequency of reading, participation in extra-curricular activities, peer influences and plans for further schooling. The APS provides key statistics to inform policy and programming activities aimed at improving the well-being of Aboriginal Peoples. It is a valuable source of information for a variety of stakeholders including Aboriginal organizations, communities, service providers, researchers, governments and the general public. The survey was carried out by Statistics Canada with funding provided by three federal departments: Aboriginal Affairs and Northern Development Canada, Health Canada and Employment and Social Development Canada (formerly called Human Resources and Skills Development Canada).